STRATEGI PENGELOLAAN LINGKUNGAN DI DANAU BUYAN KABUPATEN BULELENG - Ely Santari; Syamsul Alam Paturusi; A.A.P. Agung Suryawan (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2021)
This research aimed to determine the potential of ecotourism that can be developed and to analyze visitor perceptions and to formulate environmental management strategies for development of ecotourism in TWA Danau Buyan. The method used in this research was descriptive qualitative with the techniques, namely observation, interviews and questionnaires. The result of this indicate that the potential tourist attractions in TWA Lake Buyan area already exist including jungle tracking, camping, cannoing, selfie spot, outbond locations that have paid attention to environmental issues by involving the community. The perceptions of visitors were based on the function of the area, management policies, tourism activities, facilities and infrastructure, and on the willingness to stay generally quite good. Based on the IE table, the management strategy matrix was ??in quadrant V (Five) or in the hold and maintain and survival phase. These strategies included: a) Developing the unique potential in TWA Lake Buyan both natural resource potentials such as biodiversity (flora and fauna), landscape beauty, and community socio-cultural potential that could be developed and packaged into ecotourism package, b) Increasing support from the local government and participation of local communities to optimize the quality improvement of ODTW TWA Danau Buyan, both facilities and infrastructure tourism, public facilities, human resources, and increasing the promotion of cultural and spiritual tourism to foreign tourist, c) Increasing supervision in field, increasing guidance and counseling on the benefits of tourist attraction to the community, as well as inviting the public and tourists to actively participated in preserving the forest and existing tourism objects (environmentally friendly tourism awareness activities), d) Build cooperation and synergy with competent stakeholders, including the Tourism Office, the KSDA unit, the Agriculture Office, Academics, Non-Governmental Organization, local community organizations, and open for opportunities to do collaboration with the surrounding community. Keywords: Strategy Management, Ecotourism, Nature Tourism Park, Buyan Lake